Ungulates and carnivores from the late MIS-5 Neanderthal occupation of Gruta da Figueira Brava (Portugal) - Nabais, Mariana; Zilhão, João (Frontiers in Environmental Archaeology, 2025)
This study examines the ungulate and carnivore remains recovered from the Middle Palaeolithic site of Gruta da Figueira Brava, Portugal, to assess Neanderthal subsistence strategies in the region during late Marine Isotope Stage 5 (MIS-5). The site, now facing the Atlantic Ocean, was located up to 2 km inland at the time of occupation, providing access to both terrestrial and coastal environments. Despite extensive fragmentation and carbonate encrustation of the faunal assemblage, zooarchaeological and taphonomic analyses reveal a diversity of prey species, dominated by red deer (Cervus elaphus) and ibex (Capra pyrenaica), with lesser contributions from aurochs (Bos primigenius) and horses (Equus caballus). The skeletal element representation, along with cut marks, percussion marks and burning evidence suggest a complex and flexible approach to resource transport, processing and consumption. Neanderthals exploited both high-yield and marginal bone portions, maximising nutritional intake through cooking, defleshing and marrow extraction. The assemblage suggests that whole deer carcasses were occasionally transported to the site, while selective transport strategies were applied to larger taxa. The presence of carnivore remains, including bears (Ursus arctos), hyaenas (Crocuta crocuta), wolves (Canis lupus) and wild cats (Felis silvestris), with no evidence of human-carnivore interactions, suggests intermittent use of the cave by non-human predators during periods of human absence (e.g., for cat denning and bear hibernation or as a hyaena latrine).